Gender effects of project assessment: Evidence from a market simulation - Aquino, Karl; Deretic, Momo; Ries, John (Frontiers in Behavioral Economics, 2022)
We investigate how males and females perform as entrepreneurs and traders using information on the trading activities of students participating in a business game in two university courses. In one course, students create entrepreneurial ventures that they pitch to their peers. These students are issued securities of all the ventures and trade in a simulated market based on information revealed in the classroom pitches. In the second course, students trade these ventures in a separate simulated market but do not see pitches and trade based on anonymized written information about the ventures. We measure student performance as entrepreneurs by the traded prices of their proposed ventures in the online market and performance as traders by the value of their closing portfolios. In the course where traders observe the sales pitches of the entrepreneurial teams, we find that both male and female traders buy and sell at lower prices when the female share of the venture team increases. Females buy at higher prices and sell at lower prices than males and end up with lower portfolio values than males. None of these results obtain in the course where trading is based on the same information delivered in written and anonymized form and the gender composition of the venture teams is not known. These findings provide insight on how the assessment and performance of tomorrow's business leaders is affected by environments involving direct sales pitches.